Marital Rape: Legal And Social Perspective - Aditya Porwal (Recent Trends in Social Studies, 2024)
Worldwide, marital rape continues to be a prevalent form of sexual assault and domestic violence, defying growing international condemnation and awareness. Feminist ideologies serve as the foundation for this pervasive affliction, which rips apart victims' trust and stifles their relationships. Gender inequality continues to be prevalent in India, a country where societal norms and legal frameworks frequently fall behind. As opposed to popular belief, matrimony does not confer authorization to commit rape. Legal reforms and societal discourse must commence immediately in order to establish marital rape as a serious transgression and guarantee retribution for those who have been victimized. Advocates for consent and gender equality in matrimony must do more to prevent marital rape and advance the rights of women worldwide. In regions such as India, where gender inequality remains deeply ingrained and societal norms often lag behind legal frameworks, marital rape persists unabated. It's crucial to dispel misconceptions: marriage does not condone sexual violence. Swift legal reforms and active societal discussions are essential to acknowledge marital rape as a serious crime and ensure justice for survivors. Advocates for consent and gender equality within marriage must intensify their efforts to combat marital rape and defend women's rights globally. By prioritizing education, advocacy, and policy adjustments, societies can strive towards eradicating this egregious violation of human rights, fostering healthier and more equitable relationships for all.
Keywords: Domestic Violence; Gender inequality; Intimate relationships; Sexual assault; Women's rights; trust